Privacy-Preserving Services for Social Networks: A Review Paper (International Journal of Innovative Research in Computer Science & Technology, 2020)
The popular and frequently used Online  Social Networks (OSNs) all have a conceptually  centralized design, in which a single organization holds  unprecedented amounts of personal information in terms  of amount, variety, geographical expansion, or degree of  detail. With no need for a question, this is one of the most  serious dangers to customers' privacy or right to secrecy.  Since then, decentralization has been hailed as the solution  for privacy concerns, particularly in the world of open source networks (OSNs). A more in-depth examination of  the problem, however, indicates that, if not properly  conceived and executed, decentralization may have much  more negative impacts on users' privacy than it may bring  innovative answers. Furthermore, studies on Discrete  Online Social Networks (DOSNs) have shown that there  are additional hurdles to overcome to make them a reality,  which necessitates additional attention and novel  technological solutions. The difficulties of privacy preserving among centralization or decentralization are  discussed in this study, as well as an overview of current  research on decentralized private information social  network services.
Keywords: Decentralized Networks; nline Social Networks; Privacy Preservation; Privacy Services; Social Networking Sites